REKONSTRUKSI MATA KULIAH COMPUTER AIDED DESIGN 1 DI PROGRAM STUDI PENDIDIKAN TEKNIK MESIN UNIVERSITAS SEBELAS MARET - Abdullah Nasir Tsalasa; Yuyun Estriyanto; Taufik Wisnu Saputra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2024)
Mechanical Engineering Education study program is a study program that produces professional staff in the field of teaching and engineering who have competence in carrying out teaching processes, workshops, manufacturing processes, manufacturing drawing designs, etc. One of the courses in PTM is Computer Aided Design 1. This course is a compulsory subject that must be taken by PTM students in semester 4. The problem that occurs in this research is the implementation of learning in Computer Aided Design 1 courses in study programs The Mechanical Engineering Education of the Sebelas Maret University FKIP has not been maximized, so it is not known the degree of suitability between the implementation of the learning program and the semester learning design and the resulting output. Therefore, appropriate learning tools are needed in the learning process for CAD 2 courses. Testing the feasibility of these learning tools involves 3 parties, namely material experts, media experts, and users. From the assessment of material experts, it was obtained that the percentage of eligibility averaged 81,75% and was included in the